1995
DOI: 10.1007/bf00183695
|View full text |Cite
|
Sign up to set email alerts
|

The use of autologous free fat tissue in prevention of calvarial bone regeneration: an experimental study

Abstract: European "~1 ,,~0x °a'o' i _lflStlC bu¢ ery Abstract. Autologous free fat grafts have been successfully used to limit ingrowth of postlaminectomy fibrous tissue and to prevent reossification after bone resection in long bones. This study was designed to test the effect of placing autologous adipose tissue in standardized craniotomy defects and also to determine the effect of the presence of periosteum and dura in the area of the fat augmented defects. In 18 immature rabbits, aged 18-21 days, two identical full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Past experimental studies have revealed successful outcomes with the use of several interpositional materials in terms of prevention of early re-ossification of skull bone defects. Use of an autologous free fat graft is reportedly associated with total prevention of calvarial bone regeneration after 10 weeks after the formation of parietal bone defects (15), or 8 months after the formation of temporal bone defects in rabbits (13). Authors have noted that the use of free fat tissue transplant can be a useful alternative, serving as a biological interposition material in the surgical treatment of craniosynostosis (13,15).…”
Section: █ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Past experimental studies have revealed successful outcomes with the use of several interpositional materials in terms of prevention of early re-ossification of skull bone defects. Use of an autologous free fat graft is reportedly associated with total prevention of calvarial bone regeneration after 10 weeks after the formation of parietal bone defects (15), or 8 months after the formation of temporal bone defects in rabbits (13). Authors have noted that the use of free fat tissue transplant can be a useful alternative, serving as a biological interposition material in the surgical treatment of craniosynostosis (13,15).…”
Section: █ Discussionmentioning
confidence: 99%
“…Therefore, certain surgical techniques, such as covering of the craniectomy margins with a plastic film (8), and dural split (17), have been described in the initial studies to prevent early re-ossification at the suturectomy site after craniosynostosis surgery. Thereafter, the placement of various types of absorbable and non-absorbable materials between the bone edges as interpositional materials has been investigated in terms of their potential role in preventing early re-ossification as a useful adjunct for the treatment of craniosynostosis (1,2,4,6,13,15). These materials include polyethylene films, pericranial grafts, interpositioned biodegradable polyglycolic acid (PGA) membrane, interposed silicon membrane or expanded polytet-█ INTRODUCTION A chievement of re-ossification is the main goal of treatment in most clinical conditions with bone defects, especially in bone surgery.…”
mentioning
confidence: 99%
See 2 more Smart Citations